2020
DOI: 10.1055/s-0039-3401042
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency and Ultra-High Frequency Ultrasound: Musculoskeletal Imaging up to 70 MHz

Abstract: Musculoskeletal (MSK) ultrasound has well-established advantages, able to investigate very small structures with high resolution and a quick and real-time dynamic evaluation with the possibility of contralateral comparison. Thus ultrasound has kept its own almost exclusive fields of application in daily clinical practice, and it is considered the first-level imaging technique to assess tendons, bursae, and capsuloligamentous structures of small peripheral joints as well as peripheral nerves. Up to now, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 70 publications
0
34
0
1
Order By: Relevance
“…As in other clinical fields (18,(38)(39)(40)(41)(42)(43), UFHUS is being explored in the pSS scenario in order to evaluate its potential contribution to improve the evaluation of the SGs, particularly regarding minor SGs.…”
Section: Sgus In Ss: a Brief Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other clinical fields (18,(38)(39)(40)(41)(42)(43), UFHUS is being explored in the pSS scenario in order to evaluate its potential contribution to improve the evaluation of the SGs, particularly regarding minor SGs.…”
Section: Sgus In Ss: a Brief Reviewmentioning
confidence: 99%
“…UHFUS is a novel diagnostic technique which is finding an increasingly important role in several medical fields (18,19,(38)(39)(40)(41)(42)(43)(44)(45), including ophthalmology (38), dermatology (39,40), oral medicine (18,19,44,45), musculoskeletal (41,42) and vascular imaging (43). Since the axial resolution achievable increases with the frequency, the use of frequencies between 30-100 MHz allows to investigate superficial structures at a higher axial resolution compared to conventional US (46).…”
Section: Uhfus: Technical Notesmentioning
confidence: 99%
“…To our knowledge, the highest resolution reported for laboratory investigation of ultrasonic retinal stimulation is ~100 µm with the 43 MHz stimuli [ 54 ]. It may be possible to achieve a resolution of 30 μm with a 70 MHz transducer [ 79 , 80 ] or even a resolution of on the scale of 10 μm with a higher-frequency transducer [ 81 ]. However, previous studies indicated a reduced stimulation efficiency with the increase of the frequency.…”
Section: Spatiotemporal Characteristics Of Retinal Response To Ultmentioning
confidence: 99%
“…Ultra‐high‐frequency US transducers, with frequencies ranging from 22 to 70 MHz, provide lower resolution to 30 μm. Small structural tendon abnormalities and also tiny superficial tissues such as the pulley, retinacula, volar plate, and superficial peripheral nerve can be better assessed 34,35 …”
Section: New Us Technologiesmentioning
confidence: 99%